Characterisation of deregulated micrornas in human non-small cell lung cancer and their role in tumour angiogenesis and metastasis / Ho Chai San - Ho , Chai San (2017)
Lung cancer is the most commonly diagnosed cancer worldwide and ranks third in Malaysia with increasing mortality rate over the years. This is often due to late presentation of disease at the metastatic stage. MicroRNAs, even though are only small single-stranded non-coding RNAs, have been proven to be mighty micromanagers of gene expression in many biological processes including cancer metastasis and angiogenesis. They are comprehensively studied and thus proposed as potential molecular targets for cancer treatment. However, the mechanisms microRNA is used to modulate lung cancer metastasis remain unclear. High and low invasive A549 and SKLU- 1 sub-cell lines selected through serial transwell invasion assay for at least seven generations from their parental cell lines, were used to analyse differentially expressed metastasis-related microRNAs. Invasive phenotype in high invasive A549 and SK-LU-1 cells was found to be accompanied by gain of miR-92b and miR-378 expression as well as loss of miR-1827 expression. Investigation into the roles of these microRNAs in metastasis, particularly invasion, migration and angiogenesis, revealed that miR-378 functions as a cell invasion regulator while miR-1827 modulates cell migration. Both microRNAs work in opposite manner to mediate angiogenesis. The conversion from low invasive to high invasive phenotype by miR-378 and anti-miR-1827 was shown to involve epithelial-mesenchymal transition. MiR-92b, on the other hand, is not significant during the course of metastasis and angiogenesis in non-small cell lung cancer. Subsequently, using bioinformatics approaches, dual luciferase reporter assay and Western blotting, RBX1 and CRKL were identified as new targets of miR-378 and miR-1827, respectively. Changes in cell invasion and migratory potentials were directly controlled by RBX1 and CRKL under the negative regulation of miR-378 and miR-1827, as the repressive and inductive effects of microRNA mimics and hairpin inhibitors could be rescued by RBX1/ CRKL overexpression and knockdown. Nevertheless, restoration of RBX1 and CRKL expression only slightly reverted the angiogenic activities, suggesting that angiogenesis in non-small cell lung cancer is not only dependent on RBX1 and CRKL. These in vitro results were translated into in vivo zebrafish embryo model. MiR-378 hairpin inhibitors- and miR-1827 mimics-treated high invasive A549 cells demonstrated reduced number of metastases and ectopic vessel formation in the embryonic fish compared to negative controls. Collectively, these findings indicate that miR-378 and miR-1827 play important roles in metastasis and angiogenesis by regulating epithelial-mesenchymal transition in non-small cell lung cancer. In particular, miR-378 promotes cell invasion by targeting RBX1 while miR- 1827 suppresses cell migration by targeting CRKL. However, RBX1 and CKRL are not the major players in miR-378- and miR-1827-mediated angiogenesis.